A nomogram for predicting the development of serious bacterial infections in febrile term neonates: A single medical center experience in Southern Taiwan - Shin-Ying Li; Chun-Hao Yin; Jin-Shuen Chen; Yao-Shen Chen; Chih-Chieh Yang; Nai-Wen Fang; Hsiao-Ping Wang; Yee-Hsuan Chiou (Pediatrics and Neonatology)
Background: Serious bacterial infections (SBIs) could lead to mortality or severe long-term sequelae in neonates and infants aged <3 months. Accordingly, the aim of this study was to develop a quantitative and accurate assessment tool for predicting the risk of SBIs in febrile neonates. Methods: This retrospective study enrolled 131 febrile term neonates (aged <30 days) who were hospitalized at Kaohsiung Veterans General Hospital between January 2005 and December 2020. These neonates were classified into SBI and nonbacterial infection (NBI) groups on the basis of microbiological laboratory reports. The clinical characteristics and routine blood tests of both groups at the time of admission were analyzed. Stepwise logistic regression was applied to create and validate the nomogram for SBI prediction. Results: Among the 131 febrile neonates, 38 and 93 developed SBIs and NBIs, respectively. At the time of admission, ill clinical appearance, serum myelocyte/metamyelocyte presence, C-reactive protein (CRP) > 2.5 mg/dL, and pyuria were associated with an increased risk of SBIs. Accordingly, these four factors were used to develop a nomogram for SBI prediction, which exhibited significantly high performance (area under curve = 0.848, p < 0.001) in predicting SBI risk. Conclusion: We developed a nomogram combining clinical appearance, serum myelocyte/metamyelocyte presence, CRP, and pyuria for predicting SBI risk in febrile neonates. This tool can assist clinicians in making early diagnoses and delivering the appropriate treatment.